Roteiro de análise de situações de trabalho no processo de aprendizado em disciplinas de fisioterapia do trabalho - Shida, Georgia Jully (2012)
The Work Physioterapist much more is demonstrating its importance into the labor environment, acting out in the preventive area and also in the physical rehabilitation process. As the responsable teaching by the work placement in Work Physioterapist it has looked for a method to be followed, but none right material has found. It deals with a learning process in Work Physioterapist area that the studyings get into the classroom. The goals of this work is to help students understand occupacional health, worker health and ergonomics thoughout a construction of a analysis script of working situations to be used in the Supervised Stage in Work Physioterapist in the Physioterapist Course. The students have done two application test that allowed them be into a straight contact with the workers when they have applicated the questions, to look their working routine and its environment, to identify unright situations , when they have applicated the ergonomic tools, and even to use the classroom knowledge or surveys, and, finally, to organize all the information they have got and construct sugestions and recommendations to make goods in the working environment. The analysis script of the work situation has applicated in a gas station from Tupã SP, specifically in the clerck with the front guys and the convenience store clerk . The results of these applications were satisfactory, and also the students could have applicated the script with no dificulties. This paper deals with the phisyoterapist importance with the companies and its contribution to the worker health in a vary subject, with the general and specific aspects in a supervised stage in Work Physioterapist, its importance for vocational training, how does a stage work and what are its rules in a teaching institution. It presents a brief bibliography review about the work, work condition,ergonomics and the methods (Ergonomic Analysis of the Work, anthropometry and the ergonomics rules NIOSH, RULA, REBA, Moore and Garg, OWAS) that have served base to elaborate the script.